2020
DOI: 10.1093/mnras/staa2962
|View full text |Cite
|
Sign up to set email alerts
|

Deep model simulation of polar vortices in gas giant atmospheres

Abstract: The Cassini and Juno probes have revealed large coherent cyclonic vortices in the polar regions of Saturn and Jupiter, a dramatic contrast from the east-west banded jet structure seen at lower latitudes. Debate has centered on whether the jets are shallow, or extend to greater depths in the planetary envelope. Recent experiments and observations have demonstrated the relevance of deep convection models to a successful explanation of jet structure, and cyclonic coherent vortices away from the polar regions have… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 74 publications
4
19
2
Order By: Relevance
“…The stability of the hexagon with respect to the nearby strong storms, together with its long lifetime and survival to the strong seasonal insolation changes at its latitude, points toward a meteorological formation with roots deep in Saturn's atmosphere, as proposed by some recent models (Garcia et al, 2020;Yadava & Bloxhama, 2020). This would be consistent with the deep extension of the cloud top winds as deduced from gravity field measurements (Kaspi et al, 2020), reinforcing the idea of its possible relationship with the bulk rotation of the planet (Sánchez-Lavega, 2005, 2014.…”
Section: Data Availability Statementsupporting
confidence: 74%
“…The stability of the hexagon with respect to the nearby strong storms, together with its long lifetime and survival to the strong seasonal insolation changes at its latitude, points toward a meteorological formation with roots deep in Saturn's atmosphere, as proposed by some recent models (Garcia et al, 2020;Yadava & Bloxhama, 2020). This would be consistent with the deep extension of the cloud top winds as deduced from gravity field measurements (Kaspi et al, 2020), reinforcing the idea of its possible relationship with the bulk rotation of the planet (Sánchez-Lavega, 2005, 2014.…”
Section: Data Availability Statementsupporting
confidence: 74%
“…For the poles of Jupiter, the polygonal structure of the CPCs was modeled using a single-layer shallow water (SW) model 14 to investigate their depth and structure and provide evidence for anticyclonic shielding around the CPCs, which was shown to be necessary to inhibit cyclone mergers. In another approach, it was shown, using deep 3D models, that Jovian cyclones could extend deep and may emanate from convection of heat 15,16,17 and drift poleward 18,19 . Such 3D vortex behavior was also studied in laboratory experiments 20,21 .…”
mentioning
confidence: 99%
“…The Rayleigh number, or Ra, is the ratio of two time scales, that for diffusive thermal transport and that for convective thermal transport at a given speed, and was estimated for Jupiter to be greater than 10 12 (Manneville & Olson, 1996). One of the most recent applications of rotating thermal convective models, presented in Garcia et al (2020), for example, achieved only Ra ∼ 10 5 . It showed that deep convection can occur on Jupiter or Saturn poles, but did not reproduce the details of the observed structures or their stability.…”
mentioning
confidence: 99%